Cholangitis and pulmonary nodules in a clinical presentation of syphilis in an HIV-infected patient. (July 2019) - Hermida-Lama, Evelyn; Marco-Hernández, Javier; Medaglia, Alice Annalisa; Pagès, Mario; Vollmer, Ivan; Ramírez, Josep; Martínez, Daniel; Mallolas, Josep; García, Felipe
Several clinical manifestations attributed to syphilitic infection have been described in the literature. This is important because of the increased incidence of this infection mainly among men who have sex with men. We report the case of an HIV-infected patient who was hospitalized due to severe cholestasis, initially interpreted as drug-induced liver disease. It evolved slowly, with increasing intrahepatic cholangitis confirmed by magnetic resonance cholangiography and the appearance of several pulmonary nodules. In lung and liver biopsies, the presence of Treponema pallidum was detected by molecular and immunohistochemistry techniques, and a diagnosis of cholangitis and pulmonary syphilis was made.